Determinants of Interest in Accounting Students for a Career in Sharia Financial Institutions - Siti Nor Koidah; Indri Kartika (Journal of Islamic Economics and Finance, 2026)
This study aims to analyze the influence of sharia accounting knowledge, job market considerations, financial rewards, and religiosity on the interest of accounting students to have a career in Islamic financial institutions. This study uses a quantitative approach with primary data obtained through the distribution of questionnaires to 89 students of the Accounting Study Program, Faculty of Economics and Business, Sultan Agung Islamic University, Semarang, class of 2022 and 2023. Data analysis was carried out using multiple linear regression processed through SPSS version 25. The results of the study showed that knowledge of sharia accounting and financial awards had a positive and significant effect on the interest of accounting students in a career in Islamic financial institutions, while job market considerations and religiosity had a positive and insignificant effect. This research can be developed by improving research instruments, especially in measuring religiosity variables, as well as adding other variables such as work environment and professional practice. Accounting students are expected to increase their understanding of sharia accounting and the value of religiosity as a career provision. Islamic financial institutions are advised to increase the attractiveness of the job market through transparency of career opportunities and employee competency development.